2007
DOI: 10.1111/j.1398-9995.2007.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ARIA classification and drug treatment in allergic rhinitis and asthma

Abstract: The severity of rhinitis influences patient request for rhinitis therapy and the type of medication more than the duration. These features of rhinitis seem to poorly influence asthma therapy. As the ARIA classification is able to reveal a relevant impairment notwithstanding therapy, its role in treated patients merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
(37 reference statements)
3
17
1
2
Order By: Relevance
“…A cross-sectional study in Italy found asthma prevalence to be independent of AR severity classified by the ARIA system [33]. The same authors found weak associations between AR class and asthma therapies [34]. The group did, however, find a significant association between severity of AR and medications for AR treatment [34].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study in Italy found asthma prevalence to be independent of AR severity classified by the ARIA system [33]. The same authors found weak associations between AR class and asthma therapies [34]. The group did, however, find a significant association between severity of AR and medications for AR treatment [34].…”
Section: Reviewmentioning
confidence: 99%
“…The same authors found weak associations between AR class and asthma therapies [34]. The group did, however, find a significant association between severity of AR and medications for AR treatment [34]. …”
Section: Reviewmentioning
confidence: 99%
“…The increase in drug intake for rhinitis suggests an increase in severity from AR to AR + SwNP [25]. Moreover, the association between the severity of the upper airway diseases and the impact on asthma in the non-adjusted analysis seems to confirm the United Airways Diseases hypothesis [1,26].…”
Section: Discussionmentioning
confidence: 98%
“…Aussi, dans une étude prospective, transversale, internationale menée chez 447 patients atteints de RA, environ les deux tiers présentant une RA intermittente rapportaient une alté-ration de leur vie professionnelle ou quotidienne en raison de leurs symptômes [11]. La sévérité, plus que la durée, de la rhinite pousse généralement le patient à consulter pour être traité [12].…”
Section: Introductionunclassified